Mobile Archivists: Outreach on the Go! - Hannula, Catherine; Barth, Jennifer (KULA)

(untitled) (University of Victoria Libraries, 2018)
Despite the rich histories of rural communities in northern Wisconsin, accessibility to professional archivists is limited at best. The North Woods Tour project in Wisconsin focused on empowering local residents to preserve historical materials themselves, by teaching them basic archival methods relating to a variety of formats through personal archiving workshops. Led by Amy Sloper, head archivist at the Wisconsin Center for Film and Theater Research, three Wisconsin archivists created and implemented the project, visiting three rural northern Wisconsin communities and working with 30 local community members. This report examines their planning process and attendee response. Additionally, it argues that, in some cases, materials might be best preserved within the context of their creation.